Smelling Machine History Olfactory Experiences of Information Technology - Suominen J; Silvast A; Harviainen JT (JOHNS HOPKINS UNIV PRESS, 2022)
This article analyses users' olfactory recollections of computers, based on large-scale, online inquiry material collected between 2002 and 2003 and in 2013. It discusses how olfactory experiences and recollections can be classified based on narration and the causes of odors. Furthermore, it explores the changes of olfactory recollections over the course of ten years, and deals with age and gender in these recollections and in their representations. This project develops new paths and possibilities for studying the cultural history of technology and the collection of research material, as well as the exhibition of the history of computing by examining the historical, cultural, political, and economic dimensions of sensations and senses.